STRATEGI PENGENDALIAN BANJIR DI KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Antoni Hendra Saputra (Pelantar Press, 2024)
The development of Rumbai Pesisir Subdistrict is increasing rapidly, but the problem of flooding still exists from year to year, with new locations of flooding or higher flood intensity in some locations. Some of the factors that cause flooding in Rumbai Pesisir Sub-district are the development of the area, problematic drainage channels, plus the community's habit of throwing garbage into drainage channels. The combination of these factors causes flooding in Rumbai Pesisir sub-district. The government has made efforts to control and prevent flooding, but the efforts that have been made are still not effective because flooding still occurs frequently in Rumbai Pesisir Subdistrict. This research was conducted to analyze the factors that cause flooding, the role of the community and government in overcoming and dealing with flooding and to develop strategies needed to control flooding that occurs in Rumbai Pesisir Subdistrict using the SWOT analysis method.